Reflecting Critical Incident as a Form of English Teachers’ Professional Development: an Indonesian Narrative Inquiry Research - Alberik Ryan Tendy Wijaya; Paulus Kuswandono (IJEE (Indonesian Journal of English Education), 2018)
ABSTRACTAmidst the rapid development of English teaching, teacher’s professional development (TPD) is crucial for English teachers. It has been discussed in the TESOL Summit 2018 in Jakarta that the teachers demanded a TPD approach which facilitates them in sharing professional experiences with other teachers. This qualitative research would like to investigate the effectiveness of reflection with critical incident theory (CIT) framework as a form of TPD which many studies have found effective to fulfil that demand and yet, rarely discussed in the context of Indonesia. Based on the reviewed literature, this research applied guided reflection and interview to gather the data. The gathered data were then analysed using open-, axial-, and selective coding. From the triangulated data, five themes related to TPD were extracted. One theme is dedicated to discussing two unique cases. Overall, by reflecting their critical incidents, all of the participants could understand their experience deeper and thus, making it meaningful. Therefore, this research suggests that the utilization of reflection using CIT framework must be investigated further in a bigger scope with bigger participants and more frequencies of reflection. ABSTRAKDi tengah pesatnya perkembangan pengajaran bahasa Inggris, pengembangan profesionalisme guru (TPD) penting bagi guru Bahasa Inggris. Telah didiskusikan dalam TESOL Summit 2018 di Jakarta bahwa para guru menginginkan sebuah pendekatan TPD yang memfasilitasi mereka untuk berbagi pengalaman profesional dengan guru lainnya. Penelitian kualitatif ini ingin menginvestigasi keefektifan refleksi dengan kerangka teori peristiwa kritis (CIT) sebagai bentuk TPD yang mana banyak studi telah menemukan keefektifan untuk memenuhi permintaan tersebut, akan tetapi jarang didiskusikan di dalam konteks Indonesia. Berdasarkan tinjauan pustaka, penelitian ini mengaplikasikan refleksi terpandu dan wawancara untuk mengumpulkan data. Data yang telah terkumpul dianalisis dengan menggunakan open-, axial-, dan selective coding. Dari data yang telah ditriangulasi, terekstrak lima tema terkait TPD. Satu tema didedikasikan untuk mendiskusikan dua kasus unik. Secara keseluruhan, dengan merefleksikan peristiwa kritis, semua partisipan mampu memahami pengalaman mereka secara lebih mendalam dan oleh karenanya, membuat pengalaman tersebut bermakna. Maka dari itu, penelitian ini menganjurkan agar penggunaan refleksi dengan kerangka CIT diinvestigasi lebih lanjut dalam skala yang lebih besar dengan lebih banyak partisipan dan frekuensi refleksi yang dilakukan.     How to Cite: Wijaya, Alberik R. T., Kuswandono, P. (2018). Reflecting Critical Incident as a Form of English Teachers’ Professional Development: an Indonesian Narrative Inquiry Research. IJEE (Indonesian Journal of English Education), 5(2), 1-15. doi:10.15408/ijee.v5i2.10923